<DATA REPORT>RECORDS OF RADIO AURORA AT SYOWA STATION, ANTARCTICA IN 1986 - IGARASHI, Kiyoshi; MAENO, Hideo; SUZUKI, Akira (National Institute of Polar Research, 1988)
P(論文) departmental bulletin paper